Standards for Ocular Toxicology and Inflammation (Springer International Publishing, 2018)
This book is an international effort to standardize the language, terms, and methods used in ocular toxicology.With over 300 color illustrations this consensus volume provides standards and harmonization for procedures, terminology, and scoring schemes for ocular toxicology. It is essential for industry, pharmaceutical companies, and governmental agencies to help improve the drug development process and to reduce and refine the use of animals in research. Standards for Ocular Toxicology and Inflammation is endorsed by the American College of Veterinary Ophthalmologists.